Neuromarketing as a Secret Weapon: Increasing the Appeal of Consumer Products - Gunawan Gunawan (SEAN Institute, 2022)
This study aims to describe and analyze how neuromarketing strategies are used by business actors to enhance the attractiveness of products in the eyes of consumers. The approach used in this research is qualitative descriptive, with data collection techniques through literature review, observation, and documentation of neuromarketing practices applied in the marketing world. Neuromarketing is viewed as an approach that combines neuroscience and consumer psychology to identify emotional and cognitive responses to marketing elements such as color, packaging, advertising, and product layout. The results of the study show that neuromarketing is effective in increasing product attractiveness to consumers. Techniques such as the use of appealing visuals, appropriate music, and the application of principles like time limitation and social proof can influence consumers' emotions and purchasing decisions. Additionally, delivering simple messages and personalizing advertisements based on consumer data also play important roles in increasing engagement and purchase interest. Thus, neuromarketing can be a powerful strategy to help companies win competition in the market.